SoundEar noise warning devices cause a sustained reduction in ambient noise in adult critical care. (May 2019) - Plummer, Nicholas Russell; Herbert, Anna; Blundell, James Edward; Howarth, Rachel; Baldwin, Jacqueline; Laha, Shondipon
Introduction: Elevated sound levels in critical care are associated with sleep deprivation and an increased incidence of delirium. We aimed to determine whether a sound-activated visual noise display meter could cause a sustained reduction in sound levels overnight in an adult critical care unit. Method: Sound levels were recorded overnight for eight days before and after the introduction of a visual noise display meter, with a further eight days recorded four months later after continued use of the visual noise display meter. Results: Median ambient sound levels were significantly reduced from 57.4 dB by 3.9 dB, with a sustained reduction of 3.6 dB from baseline after four months of the device operating. Peak ambient sound levels had a small but significant reduction from 66.0 dB by 0.7 dB, with a sustained reduction of 0.8 dB after four months. Discussion: Sound-activated visual noise display meters can be effective in providing a sustained reduction in ambient sound overnight in adult critical care units, which would appear to be driven by behavioural change.